Analisis Kedwibahasaan terhadap Pembentukan Identitas Sosial Generasi Z - Endang Aristianti Gultom; Wike Afsari Sinaga; Rosenta L Situngkir; Yuliana Sari (Lembaga Pengembangan Kinerja Dosen, 2024)
This research analyzes bilingualism in the context of Generation Z's social identity formation. Using a multidisciplinary approach, this research investigates how the use of diverse languages, including bilingualism, affects the way generation Z interacts, thinks and behaves. The results show that bilingualism is not only a linguistic phenomenon, but also an important indicator in shaping a unique and dynamic social identity. The research also highlights the role of digital technology in enriching and modifying language, as well as how generation Z's social identity is formed and developed in the era of globalization. Thus, this journal makes a significant contribution in understanding the complexity of generation Z's social identity and the implications of analyzing bilingualism in the modern social context.